Bacterial Pneumonia During Pregnancy - KOCAKAYA, DERYA (Springer Nature, 2022)
The book offers a comprehensive overview of ENT diseases during pregnancy, postpartum and lactating period. It brings together the experience of authors from more than 25 countries and aims to provide a broader understanding of the diagnosis, prevention and treatment of the ENT pathologies in pregnant and lactating women. The book is organized in 7 main parts according to the ENT subspecialties, and each chapter features a reader-friendly, uniform structure. It includes developments about COVID-19 infection. ENT Diseases: Diagnosis and Treatment during Pregnancy and Lactation will appeal to a wide readership, from ENT practitioners through allergists and pulmonologists, to trainees and students in ENT, obstetrics/gynecology.​
Keywords: Postpartum period; Obstetrics; Allergic rhinitis; Sinusitis; Newborn; Lactation period; COVID-19 Antibiotics